XENIA EFFECT AND HYBRID VIGOUR IN COCONUTS - K. Satyabalan (International Coconut Community Journal, 1995)
In coconut the dried endosperin known os the copra is the most important econontic product os it is from the copra, oil is extracted by crushing. To increase the copra content in coconut Haldane (1958) had suggested that it should be possible to compare the size, oil content and other characteristics of the nut borne on the same tree after using pollen from two different pollen parents. The also indicated that the hybrid vigour may possibly show in nuts derivedfrom cross pollination since hybrid vigour in some species is largely due to increased seed weight. If so, it is possible that a mixed plantation may produce a better crop than either of the two breeds when grown alone. Studies on the nut and copra characteristics of Tall x Dwarf hybrids and their reciprocals with their parents in coconut have indicated the importance of selection of pollen parents for producing proinising hybrids which will give better yields and also nuts of better quality and quantity of copra. Hence in copra improvement progrannne by hybridization, selection of parents is of great importance for the production of hybrids which will not only give high yield of nuts and also yield higher outturn of good quality copra. Attempts have been made to identify the best combinersfor the production of high yielding hybrids. Restilts obtained are discussed in this paper.